Comprehensive characterization of the brain proteome of a 6-OHDA animal model: new insights into Parkinson's disease - Silva, Sofia Cristóvão Alves Fernandes da (2019)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia